Interface Molecules of Angiostrongylus cantonensis: Their Role in Parasite Survival and Modulation of Host Defenses - Alessandra L. Morassutti; Carlos Graeff-Teixeira (International Journal of Inflammation)
Angiostrongylus cantonensis is a nematode parasite that causes eosinophilic meningoencephalitis in humans. Disease presents following the ingestion of third-stage larvae residing in the intermediate mollusk host and disease manifests as an acute inflammation of the meninges characterized by eosinophil infiltrates which release a battery of proinflammatory and cytotoxic agents in response to the pathogen. As a mechanism of neutralizing these host defenses, A. cantonensis expresses different molecules with immunomodulatory properties that are excreted or secreted (ES). In this paper we discuss the role of ES proteins on disease exacerbation and their potential use as therapeutic targets.